The Potential of Bioactive Compound Moringa Leaf to Improve Rabbit Reproductive Performance - Setiasih Setiasih; Ahmad Mualif Abdurrahman; Hendrawan Soetanto (Indonesian Center for Animal Research and Development, 2021)
Moringa leaf is a potential animal feed material because it has a complete nutrient content as well as many bioactive compounds. Among its bioactive compounds are phytosterols and isoflavones. This paper aims to describe the importance of moringa leaf as feed supplementation to improve rabbit reproductive performance. The bioactive compounds in moringa leaf have an important role to trigger reproductive hormones.. Phytosterols have a chemical structure similar to that of cholesterol that can be used as precursors of steroid hormones (testosterone, estradiol and progesterone). Isoflavones are one of the flavonoid compounds, also have estrogenic activity and are able to bind with estrogen receptors i.e. ER-α and ER-β. Because of these bioactive compounds, moringa leaves are potential to be utilized as feed supplements as aphrodisiac for bucks, stimulating estrous, and increasing litter size and milk production of does, reduce mortality and increase weaning weight and average daily gain of bunnies.